PEMBINAAN PEMBELAJARAN SEBAGAI SALAH SATU UPAYA PENINGKATAN KOMPETENSI PEDAGOGIK BAGI GURU-GURU PAUD NAVA DHAMMASEKHA KARUNA, TELUKNAGA, TANGERANG - Astana, Astri Chintya; Susijati, Susijati; Sihombing, Trifena R. Clara (Community Services and Social Work Bulletin, 2022)
An important component in learning and learning activities is the educator, or teacher. Teachers play a very important role because they function as mentors who deliver and transfer teaching materials in the form of knowledge. The teacher also determines the success of the students related to the teaching and learning process. It is required that teachers improve quality and professionalism. One of its competencies is pedagogic competence, which is the ability of teachers to manage student learning, which includes understanding insights or educational foundations, understanding of students, developing curriculum or a syllabus, learning design, implementing educational and dialogical learning, utilizing learning technology, and evaluating learning outcomes. Not all Nava Dhammasekha teachers have a background in early childhood education. Based on this background, the author was encouraged to do service to the Nava Dhammasekha Karuna school, Teluk Naga Tangerang. This community service activity is intended to provide training and coaching aimed at helping teachers improve their pedagogical competence.